Virosome: An engineered virus for vaccine delivery - Hasan Ali; Md. Akbar; Babar Iqbal; Faraat Ali; Neeraj Kant Sharma; Nitin Kumar; Asim Najmi; Mohammed Albratty; Hassan A. Alhazmi; Osama A. Madkhali; Khalid Zoghebi; Md Shamsher Alam (Elsevier, 2023)
The purpose of immunization is the effective cellular and humoral immune response against antigens. Several studies on novel vaccine delivery approaches such as micro-particles, liposomes & nanoparticles, etc. against infectious diseases have been investigated so far. In contrast to the conventional approaches in vaccine development, a virosomes-based vaccine represents the next generation in the field of immunization because of its balance between efficacy and tolerability by virtue of its mechanism of immune instigation. The versatility of virosomes as a vaccine adjuvant, and delivery vehicle of molecules of different nature, such as peptides, nucleic acids, and proteins, as well as provide an insight into the prospect of drug targeting using virosomes. This article focuses on the basics of virosomes, structure, composition formulation and development, advantages, interplay with the immune system, current clinical status, different patents highlighting the applications of virosomes and their status, recent advances, and research associated with virosomes, the efficacy, safety, and tolerability of virosomes based vaccines and the future prospective.